PRIMARY (GENETICALLY DETERMINED) DILATION CARDIOMYOPATHY IN A PATIENT WITH NOVEL MUTATION OF LAMIN GENE: CLINICAL AND MORPHOLOGICAL MANAGEMENT - O. V. Blagova; I. N. Alieva; A. V. Nedostup; V. A. Sulimov; E. A. Kogan; A. G. Shestak; D. A. Zateyshchikov; E. V. Zaklyazminskaya (Кардиоваскулярная терапия и профилактика)
The primary diagnosis of “dilation cardiomyopathy” is syndromal, and demands clarification of nosological origins. In the article, the specifics of such diagnostics is discussed. Clinical case is provided that illustrates the ways of management, diagnostics and treatment of the essential (primary, genetically determined) dilation cardiomyopathy. Patient of 22 year old with no family history, at the ages 20 and 21 y.o. had cardioembolic strokes. Paroxysmal atrial fibrillation was found, raised creatine kinase levels up to 349-1045 U/L, decreased ejection fraction 17%. Heart failure rapidly progressed. In endomyocardial biopsy there was homogenisation of cardiomyocytes, subendocardial lipomatosis with borderline virus-negative myocarditis. By Senger direct sequencing, the novel variant p.E372 in gene LMNA was found, heterozygous. Implantation of CRT-D was done, and in 4 months — cardiac transplant.